Bifidobacterial Dialogue With Its Human Host and Consequent Modulation of the Immune System - Alessandri, Giulia; Ossiprandi, Maria Cristina; MacSharry, John; van Sinderen, Douwe; Ventura, Marco (Frontiers in Immunology, 2019)
Since bifidobacteria are among the pioneering colonizers of the human infant gut, their interaction with their host is believed to start soon following birth. Several members of the Bifidobacterium genus are purported to exert various health-promoting effects at local and systemic levels, e.g. limiting pathogen colonization/invasion, influencing gut homeostasis and influencing the immune system through changes in innate and/or adaptive immune responses. This has promoted extensive research efforts to shed light on the precise mechanisms by which bifidobacteria are able to stimulate and interact with the host immune system. These studies uncovered a variety of secreted or surface-associated molecules that act as essential mediators for the establishment of a bifidobacteria-host immune system dialogue, and that allow interactions with mucosa-associated immune cells. Additionally, the by-products generated from bifidobacterial carbohydrate metabolism act as vectors that directly and indirectly trigger the host immune response, the latter by stimulating growth of other commensal microorganisms such as propionate- or butyrate-producing bacteria. This review is aimed to provide a comprehensive overview on the wide variety of strategies employed by bifidobacteria to engage with the host immune system.